ANALISIS SEMIOTIKA PESAN DAKWAH DALAM FILM CINTA SUBUH KARYA INDRA GUNAWAN - Apriliyana Apriliyana (ADISAM PUBLISHER, 2023)
Cinta Subuh is an Indonesian film in 2022 directed by Indra Gunawan. This film, based on a novel by Ali Farighi, stars Dinda Hauw, Roger Danuarta and Rey Mbayang. The film Cinta Subuh will be released in theaters on May 19, 2022. The type of research used is a qualitative approach where this type of research seeks to collect facts, data or information and explore facts, data and information with certain scientific techniques. The data analysis technique used is media text analysis with Charles Sanders Pierce's semiotic analysis model. Based on the results of research conducted on